The Dutch patient-based Constant Murley score cannot be used interchangeably with the clinician-based Constant Murley score in shoulder arthroplasty patients - Hesseling, Brechtje; Perry, Sander I.B.; Hoelen, Max A.; van Deurzen, Derek F.P.; Eygendaal, Denise; Mathijssen, Nina M.C.; Snoeker, Barbara A.M. (Journal of Shoulder and Elbow Arthroplasty, 2026)
Background: To find an alternative for the time-consuming Dutch clinician-based Constant Murley score (c-CMS), we assessed its interchangeability with the patient-based CMS (p-CMS) in patients undergoing arthroplasty. Also, we assessed test-retest reproducibility of both CMS versions. Methods: The English p-CMS was translated into Dutch using forward and backward translation. We administered the c-CMS and p-CMS at 2 time points before surgery and 6 months after surgery. Subsequently, we calculated absolute agreement parameters, both between p-CMS and c-CMS, to study interchangeability. For the repeated measurements of c-CMS and p-CMS, agreement was calculated separately to study test-retest reproducibility. Results: We recruited 139 patients from 3 different hospitals. Between total p-CMS and total c-CMS, the 95% limits of agreement (LoAs) were −20.4 to 22.6 with a mean bias of 1.1. For test-retest reproducibility of the c-CMS and the p-CMS, LoAs were −15.1 to 15.7 (mean bias 0.3) and −16.6 to 18.8 (mean bias 1.1), respectively. These LoAs were all wider than the shoulder arthroplasty−specific Minimal Clinically Important Differences found in the literature. Conclusion: The p-CMS cannot be used interchangeably with the c-CMS. In addition, the CMS has become obsolete for quantifying shoulder functionality; shoulder-specific patient-reported outcome measures with better reproducibility are currently available.
Keywords: Agreement; Clinimetric study; Constant Murley score; Level III; Prospective Cohort Study; Shoulder arthroplasty; Test-retest reproducibility